Pre-operative management of Pleomorphic and florid lobular carcinoma in situ of the breast: Report of a large multi-institutional series and review of the literature - Foschini, Maria P; Miglio, Rossella; Fiore, Roberta; Baldovini, Chiara; Castellano, Isabella; Callagy, Grace; Bianchi, Simonetta; Kaya, Handan; Amendoeira, Isabel; Querzoli, Patrizia; Poli, Francesca; Scatena, Cristian; et al. (European journal of surgical oncology, 2019)
BACKGROUND: Pleomorphic and Florid Lobular carcinoma in situ (P/F LCIS) are rare variants of LCIS, the exact nature of which is still debated. AIM: To collect a large series of P/F LCIS diagnosed on preoperative biopsies and evaluate their association with invasive carcinoma and high grade duct carcinoma in situ (DCIS). Data obtained were compared with those reported in the literature. METHODS: A multi-institutional series of P/F LCIS was retrieved. All cases were diagnosed on pre-operative biopsies, which was followed by an open surgical excision. Data on post-operative histopathology were available. A literature review was performed. RESULTS: A total of 117 cases were collected; invasive carcinoma and/or DCIS was present in 78/117 cases (66.7%). Seventy cases of P/F LCIS were pure on biopsy and 31 of these showed pathological upgrade in post-surgical specimens. Pre-operative biopsy accuracy was 47/78 (60.3%); pre-operative biopsy underestimation of cancer was 31/78 (39,7.%). In the literature review papers, invasive carcinoma or DCIS was associated with 274 of 418 (65.5%) cases of P/F LCIS. Pre-operative biopsy accuracy was 66% (181/274) whereas pre-operative biopsy underestimation of cancer was 33.9% (93/274). CONCLUSIONS: The data presented here indicate that P/F LCIS is frequently associated with invasive carcinoma or high grade DCIS and that pre-operative biopsy is associated with an underestimation of malignancy. Open surgery is indicated when P/F LCIS is diagnosed pre-operatively.
Keywords: senioři; Carcinoma, Ductal, Breast; Neoplasm Invasiveness; karcinom prsu in situ; Breast Neoplasms; senioři nad 80 let; Europe; Neoplasm Grading; Evropa; Carcinoma, Intraductal, Noninfiltrating; resekční okraje; Middle Aged; Biopsy; Carcinoma, Lobular; Margins of Excision; Adult; Pleomorphic lobular carcinoma in situ; lobulární karcinom; Aged, 80 and over; duktální karcinom prsu; Pre-operative biopsy; intraduktální neinfiltrující karcinom; ženské pohlaví; Florid lobular carcinoma in situ; Lobular carcinoma in situ; Humans; Breast Carcinoma In Situ; Breast cancer screening; invazivní růst nádoru; lidé středního věku; stupeň nádoru; nádory prsu; biopsie; dospělí; Female; Aged; lidé